Improved Charge Extraction Beyond Diffusion Length by Layer‐by‐Layer Multistacking Intercalation of Graphene Layers inside Quantum Dots Films. Issue 14 (13th February 2019) - Chen, Wenjun; Castro, Joshua; Ahn, Seungbae; Li, Xiaochen; Vazquez‐Mena, Oscar
Abstract: Charge collection is critical in any photodetector or photovoltaic device. Novel materials such as quantum dots (QDs) have extraordinary light absorption properties, but their poor mobility and short diffusion length limit efficient charge collection using conventional top/bottom contacts. In this work, a novel architecture based on multiple intercalated chemical vapor deposition graphene monolayers distributed in an orderly manner inside a QD film is studied. The intercalated graphene layers ensure that at any point in the absorbing material, photocarriers will be efficiently collected and transported. The devices with intercalated graphene layers have superior quantum efficiency over single‐bottom graphene/QD devices, overcoming the known restriction that the diffusion length imposes on film thickness. QD film with increased thickness shows efficient charge collection over the entire λ ≈ 500–1000 nm spectrum. This architecture could be applied to boost the performance of other low‐cost materials with poor mobility, allowing efficient collection for films thicker than their diffusion length. Abstract : A novel architecture based on layer‐by‐layer multistacking intercalation of graphene inside quantum dot (QD) films is studied. The intercalated graphene layers ensure improved charge extraction beyond the diffusion length of the QDs, offering superior quantum efficiency over single‐bottom graphene/QD devices, and overcoming the restriction that the diffusion length imposes on film thickness.